The enhanced six-port receiver: A new concept for simultaneous data reception and direction of arrival detection - Kölpin, Alexander; Vinci, Gabor; Lämmle, Benjamin; Weigel, Robert (International Microwave Symposium 2011, 2011)
The key benefits of the six-port receiver architecture, being a special type of direct conversion receivers, are its high bandwidth and low circuit complexity. This concept has been known on the one hand for precise phase measurement applications and on the other hand for complex valued data reception in the millimeter wave region. The work presented here shows a new approach for combining both principles in one six-port receiver. For the first time a method for simultaneous data reception and direction of arrival (DOA) detection will be presented requiring only one enhanced six-port front-end.
elib2cris::1512001600,koelpin2011
Keywords: Ad hoc networks; Antennas; Equations; Microwave Circuits; Microwave Communication; Receivers; Direction of arrival; Six-Port